INFORMATION SUPPORT FOR REFLEXIVE MANAGEMENT OF BUSINESS PROCESSES OF AGRICULTURAL ENTERPRISES IN CONDITIONS OF DIGITALIZATION - HRYNOVETS, Markian; KUCHER, Lesia; KUCHER, Anatolii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This paper provides a theoretical justification for information support for reflexive management of business processes of agricultural enterprises in the context of digitalization based on an integrated approach. The information and analytical needs of agribusiness subjects have been identified and systematized. The data on common software products for collecting, processing, using and storing information by its types that can be used by agricultural enterprises are summarized. The article argues that the effectiveness of information support for reflexive management of business processes of agricultural enterprises in conditions of digitalization largely depends on the systematization, structuring, and diversification of information. These aspects enable agricultural enterprises to adapt to changing business conditions, optimize production processes, efficiently manage resources, and forecast operational outcomes. A comprehensive approach to information support, which includes the integration of various software products, enhances the management efficiency of agricultural enterprises, despite potential challenges related to system compatibility and integration. It is substantiated that agricultural enterprises should focus on the constant updating and modernization of their information systems, adapting them to the latest technologies, market demands, and their own informational needs. Another important aspect is the development of staff skills in utilizing these systems, ensuring their effective application. Finally, strategic planning and data analysis from information systems can become key factors in making well-founded management decisions, increasing the competitiveness and efficiency of the agricultural enterprise.
Keywords: reflexive approach; management of business processes; digitization of business processes; information support; information systems; risk management; management of agricultural enterprises; agribusiness